The Effect of Preincubation Time and Myo-inositol Supplementation on the Quality of Mouse MII Oocytes - Mohammadi, Fatemeh; Ashrafi, Mahnaz; Zandieh, Zahra; Najafi, Mohammad; Niknafs, Behrooz; Amjadi, Fatemeh Sadat; Haghighi, Maryam (Journal of Reproduction & Infertility, 2020)
Background: It is demonstrated that optimal preincubation time improves oocyte quality, fertilization potential and developmental rate. This study aimed to evaluate the effect of preincubation time in the simple and myo-inositol supplemented medium on the oocyte quality regarding oxidative stress and mitochondrial alteration. Methods: Cumulus oocyte complexes (COCs) retrieved from superovulated NMRI mice were divided in groups of 0, 4 and 8 hr preincubation time in the simple and 20 mmol/L myo-inositol supplemented media. Intracellular reactive oxygen species (H2O2), glutathione (GSH), mitochondrial membrane potential (MMP), ATP content, and mitochondrial amount were measured and analyzed in experimental groups. One-way ANOVA and Kruskal-Wallis were respectively used for parametric and nonparametric variables. Statistical significance was defined as p<0.05. Results: In comparison to control group, variables including ROS, GSH, mitochondrial amount, fertilization and developmental rates were significantly changed after 4 hr of preincubation in the simple medium, while MMP decreased following 8 hr of preincubation in the simple medium (p˂0.001). Preincubation of oocytes up to 8 hr in the simple medium could not decrease ATP content. For both 4 and 8 hr preincubation times, myo-inositole could decrease H2O2 and increase GSH and MMP levels and consequently could improve fertilization rate compared to oocytes preincubated in the simple culture. Conclusion: It seems that 4 hr or more preincubation time can decrease the oocyte quality and lead to reduced oocyte fertilization and developmental potential. Howevere, myo-inositol may prevent oocyte quality reduction and improve fertilization potential in comparision to the equivalent simple groups.